Relationship between HALP and PNI score with 1-month mortality after CABG - Koyuncu, Ilhan; Koyun, Emin (Frontiers in Nutrition, 2024)
Background Coronary heart disease (CHD) is the most common cause of cardiovascular disease (CVD). CHD is among the most common causes of mortality and morbidity world wide. In addition, CHD is one of the most important causes of health expenditures world wide. Today, coronary artery bypass grafting (CABG) operations are a widely used surgical procedure and have an important place in the treatment of CHD. Many scoring systems have been evaluated to estimate the risk of mortality and morbidity. 30-day mortality rates after CABG have been reported as 1–4% in large-scale studies. Objectives The aim of our study was to evaluate the relationship between 1-month mortality in patients undergoing CABG and the Hemoglobin, albumin, lymphocyte, platelet index (HALP score) and Prognostic nutritional index (PNI) calculated using laboratory data in the preoperative period. Methods and design A total of 239 patients who underwent CABG were evaluated retrospectively. Preoperative biochemical and hemogram values, demographic characteristics, comorbidities, HALP score and PNI values of the patients were recorded. The patients were divided into two groups: Exitus group (n = 51) and survival group (n = 188). The data of the two groups were compared, mainly HALP score and PNI. Results It was observed that 51 of 239 patients (21.3%) developed exitus during the 30-day follow-up after CABG. When demographic data are compared; advanced age, female gender, history of DM (Diabetes Mellitus), history of HL (hyperlipidemia) and smoking were found to be associated with mortality. When laboratory data are compared; high troponin levels, low hemoglobin, low lymphocyte and low albumin levels were found to be associated with mortality. Low HALP score (p < 0.001) and low PNI (p < 0.001) were also found to be associated with mortality. In univariate and multivariate regression analysis; advanced age, history of DM, HALP score and PNI were found to be independent predictors of 30-day mortality after CABG. It was determined that a cut-off value of 0.29 for the HALP score and 39.1 for PNI had found, respectively, 81 and 79% sensitivity and 82 and 80% specificity. Conclusion Preoperatively measured HALP score and PNI can be used to predict 1-month mortality after CABG.